Prevalence of PfATPase6 Gene Mutation for ACT Resistance in Plasmodium falciparum Malaria Parasites among Patients with Fever in Osun State Health Facilities, Nigeria - Olufemi Oroge; Sunday Olarewaju; Adeola Olukosi; Akinlabi Rufai; Sukurat Oyebanji; Ayo Fasasi; Akinwale Faniyi; Monsuru Adeleke (Journal of Genetic Resources)
Malaria remains a significant public health challenge in Nigeria, particularly in Osun State, where Plasmodium falciparum is the predominant species responsible for the disease. This research aimed to assess the prevalence of Plasmodium falciparum ATPase 6 gene (PfATPase6) mutations associated with artemisinin-based combination therapy (ACT) resistance in P. falciparum isolates from febrile patients attending health facilities across eight local government areas (LGAs) in Osun State, Nigeria. A cross-sectional study was conducted across eight LGAs in Osun State, where between 36 and 40 febrile patients were randomly selected from each local government area. A total of 315 respondents (175 females and 140 males) participated, with a mean age of 16.7 years. Rapid diagnostic tests (RDTs) for malaria were performed, and samples from positive cases were analyzed for the presence of PfATPase6 gene mutations using polymerase chain reactions. Out of 293 valid malaria RDTs conducted, 127 (43.3%, CI 37.59%-49.23%) tested positive for P. falciparum. The mean age of patients who tested positive was 11.12 years, which was statistically significant (p < 0.05). The highest malaria prevalence rate was recorded in Orolu LGA (57.5%), while the lowest was in Osogbo LGA (29.41%). Socio-demographically, malaria prevalence was highest among respondents with no more than primary school education (59.7%). Notably, none of the 127 P. falciparum positive samples harbored the PfATPase6 gene mutation. The study reveals a substantial burden of malaria in Osun State, particularly among younger patients and those with lower educational attainment. However, the absence of PfATPase6 gene mutations in all positive samples suggests that ACTs remain effective in this region.